2002
DOI: 10.1046/j.1445-2197.2002.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in elective colorectal surgery

Abstract: These results suggest that a significant proportion of surgeons administer excessive and unnecessary doses of antibiotics in elective colorectal surgery. Further studies are required to uncover the reasons but lack of appropriate guidelines and failure to exercise evidence-based medicine are major factors that account for this practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…42 A survey conducted among Malaysian general surgeons (n = 96) found 40 respondents (42%) claimed that their basis of drug scheduling was influenced by medical literature. 41 However, of these 40 surgeons, only 9.5% administered a single dose of prophylactic antibiotic. Other factors affecting their drug scheduling was hospital guidelines (32%), personal preference (22%) and similar scheduling by colleagues (4%).…”
Section: Studies Exploring Surgeons' Adherence To Sap Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A survey conducted among Malaysian general surgeons (n = 96) found 40 respondents (42%) claimed that their basis of drug scheduling was influenced by medical literature. 41 However, of these 40 surgeons, only 9.5% administered a single dose of prophylactic antibiotic. Other factors affecting their drug scheduling was hospital guidelines (32%), personal preference (22%) and similar scheduling by colleagues (4%).…”
Section: Studies Exploring Surgeons' Adherence To Sap Guidelinesmentioning
confidence: 99%
“…Other factors affecting their drug scheduling was hospital guidelines (32%), personal preference (22%) and similar scheduling by colleagues (4%). 41 Around 30% of surgeons mentioned that there was no antibiotic policy at their hospital. This finding suggested that formal SAP protocols are either unavailable or poorly disseminated at their hospital.…”
Section: Studies Exploring Surgeons' Adherence To Sap Guidelinesmentioning
confidence: 99%
“…A similar situation or higher rates of surgical antimicrobial prophylaxis >24 h have been reported in other countries (range 52.8–77%) [ 11 , 12 , 20 , 21 , 22 ]. A survey conducted among general surgeons found that failure to keep up to date, reliance on habit rather than on evidence-based practices, personal experience and preference, peer influence, and institutional norms affected their choice of duration of antimicrobials cover [ 23 ]. Prolonging antimicrobial prophylaxis >24 h for most surgical procedures does not prevent the development of postoperative infections compared to recommended duration (24 h or less).…”
Section: Discussionmentioning
confidence: 99%
“…While the adverse clinical impacts include increased hospital costs borne by the patients, the adverse clinical impacts include the occurrence of surgical site infections, prolonged hospital stay, increased consumption of antibiotics, the emergence of antibiotic resistance, morbidity and mortality (75,76). Also, previous studies have shown that in the absence of guidelines the prescribing patterns of physicians for SAP tend to be based on diverse rationales such as personal preferences, medical literature (77), discussions with colleagues (78) etc. In addition, there is a misconception among some surgeons that prolonged regimens with multiple antibiotics are more effective than short courses of narrow-spectrum antibiotics in reducing or eliminating the risk of surgical site infections (79).…”
Section: Challenges Regarding the Practice Of Surgical Antibiotic Pro...mentioning
confidence: 99%